Penemuan Makna Hidup Sebagai Solusi Atas Fenomena N.E.E.T: Refleksi Filosofis Novel Re: Zero Melalui Pemikiran Eksistensialisme Viktor Frankl: Finding the Meaning of Life as a Solution to the N.E.E.T Phenomenon: Philosophical Reflections on the Novel Re: Zero Through Viktor Frankl's Existentialist Thought - Wintama, Idrus (Jurnal Filsafat Indonesia, 2024)
This research delves into the profound search for the meaning of life behind suffering in the light novel Re: Zero Kara Hajimeru Isekai Seikatsu or Re: Zero by Nagatsuki Tappei, using the existentialist philosophy of Viktor Frankl. In a world grappling with social issues like the N.E.E.T. phenomenon, where many individuals are not in education, employment, or training, the author asserts that understanding the meaning of life is crucial, especially for teenagers. This article employs qualitative research methods, specifically literature review methods, which use literature as a foundation for data collection. The findings reveal that the analysis of the novel Re: Zero through Viktor Frankl's lens unveils the unwavering attitude of Natsuki Subaru, the protagonist, in his quest to find meaning in suffering, a perspective applicable to all. Natsuki Subaru's character can also serve as a beacon of inspiration, particularly for teenagers, in navigating life's hardships by fostering an optimistic outlook in the face of adversity.